2020
DOI: 10.1007/s42843-020-00003-4
|View full text |Cite
|
Sign up to set email alerts
|

Adventure Therapy Treatment for Young Adult Males Struggling with Addictions

Abstract: Adventure therapy is the prescriptive use of adventure experiences conducted in natural settings by mental health professionals that kinesthetically engage clients on cognitive, affective, and behavioral levels. Meta-analyses, specific research on skills developed through the experience, and theoretically reasoned factors inherent in the adventure therapy experience suggest that adventure therapy is a promising treatment option for adolescents and young adults. AT treatment programs are slowly gaining traction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Adventure therapy employs the natural environment and adventure-based sports activities as an experiential, interactive model, aiding in emotional healing. Research indicates that adventure therapy is a viable and promising treatment approach by fostering autonomy, life skills, a sense of accomplishment and a sense of responsibility in real-life situations [ 23 , 41 , 42 ].…”
Section: Integrating Exercise With Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adventure therapy employs the natural environment and adventure-based sports activities as an experiential, interactive model, aiding in emotional healing. Research indicates that adventure therapy is a viable and promising treatment approach by fostering autonomy, life skills, a sense of accomplishment and a sense of responsibility in real-life situations [ 23 , 41 , 42 ].…”
Section: Integrating Exercise With Therapeutic Approachesmentioning
confidence: 99%
“…Instead of receiving direct orders, learners are encouraged to discover and participate in group projects, and simulations of real-world situations co-constructing their experiences, enhancing self-awareness about their decisions and outcomes, and integrating routines and monitoring into their practice during daily tasks in wilderness settings. Research indicated that therapeutic outdoor interventions have increased in popularity as alternative approaches for treating at-risk or adjudicated adolescents [ 41 , 59 , 60 ].…”
Section: Integrating Exercise Into Sud Recovery: Cognitive–behavioral...mentioning
confidence: 99%